Fault Location Scheme for Abnormal Grounding Point in Isolated Ground Wire of Large-Scale Clean Energy Transmission - Wang, Yunlong; Chen, Nuo; Ma, Xiangnan; Yang, Zongzhang (Frontiers in Energy Research, 2021)
There are a lot of grounding switches along the isolated ground wire for the de-icing in the large-scale wind farm. If any grounding switches are forgotten to be open, there will be unexpected abnormal grounding point in the isolated ground wire. Based on the analysis of the output power of de-icing devices, the output power of different poles can be applied for the abnormal grounding point fault location. Since the rising of output current to the rated current of de-icing devices requires a long time, the protective relay may lock the de-icing device before the output current reaching rated current. Thus, the ratio of output energy of two poles is selected to locate the abnormal grounding point. This location method is verified by a large number of simulations.